Poverty, Education, and Health in Indonesia : Who Benefits from Public Spending? - Lanjouw, Peter (World Bank, Washington, DC, 2014)
The authors investigate the extent to which Indonesia's poor benefit from public and private provisioning of education and health services. Drawing on multiple rounds of SUSENAS household surveys, they document a reversal in the rate of decline in poverty and a slowdown in social sector improvements resulting from the economic crisis in the second half of the 1990s. Carrying out traditional static benefit-incidence analysis of public spending in education and health, the authors find patterns consistent with experience in other countries: spending on primary education and primary health care tends to be pro-poor, while spending on higher education and hospitals is less obviously beneficial to the poor. These conclusions are tempered once one allows for economies of scale in consumption which weaken the link between poverty status and household size. The authors also examine the incidence of changes in government spending. They find that the marginal incidence of spending in both junior and senior secondary schooling is more progressive than what static analysis would suggest, consistent with "early capture" by the non-poor of education spending. In the health sector marginal and average incidence analysis point to the same conclusion: the greatest benefit to the poor would come from an increase in primary health care spending.